Efficacy, safety, and immunogenicity of the Shigella sonnei 1790GAHB GMMA candidate vaccine: Results from a phase 2b randomized, placebo-controlled challenge study in adults. (September 2021) - Frenck, Robert W.; Conti, Valentino; Ferruzzi, Pietro; Ndiaye, Augustin G.W.; Parker, Susan; McNeal, Monica Malone; Dickey, Michelle; Granada, Juan Paolo; Cilio, Giulia Luna; De Ryck, Iris; Necchi, Francesca; Suvarnapunya, Akamol E.; et al.
Abstract: Background: Shigellosis accounts for substantial morbidity and mortality worldwide and is the second most common cause of moderate and severe diarrhoea in children. Methods: This phase 2b study (NCT03527173), conducted between August 2018 and November 2019, evaluated vaccine efficacy (VE), safety, and immunogenicity of a Shigella sonnei GMMA candidate vaccine (1790GAHB) in adults, using a S. sonnei 53 G controlled human infection model. Participants (randomized 1:1) received two doses of 1790GAHB or placebo (GAHB-Placebo), at day (D) 1 and D29, and an oral challenge of S. sonnei 53 G at D57. VE was evaluated using several endpoints, reflecting different case definitions of shigellosis. For the primary endpoint, the success criterion was a lower limit of the 90% confidence interval >0. Findings: Thirty-six and 35 participants received 1790GAHB or placebo, respectively; 33 and 29 were challenged, 15 and 12 developed shigellosis. VE was not demonstrated for any endpoint. Adverse events were more frequent in 1790GAHB versus placebo recipients post-vaccination. Anti- S. sonnei lipopolysaccharide (LPS) IgG responses increased at D29 and remained stable through D57 in group 1790GAHB; no increase was shown in placebo recipients. Interpretation: 1790GAHB had an acceptable safety profile and induced anti-LPS IgG responses but did not demonstrate clinical efficacy against shigellosis. Baseline/pre-challenge antibody levels were higher in participants who did not develop shigellosis post-challenge, suggesting a role of anti-LPS IgG antibodies in clinical protection, although not fully elucidated in this study. For further vaccine development an increased S. sonnei O-antigen content is likely needed to enhance anti-LPS immune responses. Funding: GlaxoSmithKline Biologicals SA, Bill and Melinda Gates Foundation